Overhead transmission line outage rate estimation under wind storms. Issue 1 (17th July 2018) - Liu, Yang; Lei, Shunbo; Hou, Yunhe
Abstract : Wind storms such as hurricanes increase the outage rate of overhead transmission lines and hence can seriously affect the security of power systems. Therefore, it is very important to estimate the overhead transmission line outage rate for a power system that might be jeopardized by wind storms. In this paper, we propose a new method for estimating the outage rate of overhead transmission lines, with two primary advantages. First, the proposed method describes the relationship between the outage rate and the weather factors by a fragility curve customized for overhead transmission lines to ensure that the relationship is precisely represented. Second, the proposed method takes the conductor strength reduction and different physical properties of overhead transmission lines into consideration to increase outage rate estimation accuracy. We test the proposed method by estimating the outage rate of overhead transmission lines in a regional power system based on both historical and simulated wind storms. The test results show that the proposed method generates a more accurate estimation than the conventional approaches. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.